Everything is now : revolutionary ideas from string theory - Spence, D. W. (David William) (Boca Raton, FL : CRC Press, 2021)
This engaging and beautifully written book gives an authoritative but accessible account of some of the most exciting and unexpected recent developments in theoretical physics. - Professor Lionel J Mason, Mathematical Institute, University of Oxford String theory is often paraded as a theory of everything, but there are a large number of untold stories in which string theory gives us insight into other areas of physics. Here, Bill Spence does an excellent job of explaining the deep connections between string theory, particle physics, and the novel way of viewing space and time. - Professor David Tong, Department of Applied Mathematics and Theoretical Physics, University of Cambridge Foremost amongst Nature's closest-guarded secrets is how to unite Einstein's theory of gravity with quantum theory - thereby creating a quantum space-time'. This problem has been unsolved now for more than a century, with the standard methods of physics making little headway. It is clear that much more radical ideas are needed, and our front-line researchers are showing that string theory provides these. This book describes these extraordinary developments, which are helping us to think in entirely new ways about how physical reality may be structured at its deepest level. Amongst these ideas are that Everything can happen at the same time - it is all Now; Hidden spaces, large and small, are everywhere amongst us; The basic objects are membranes' that behave like soap bubbles and can explore the shape of spacetime in new ways; We are holographic projections from higher dimensions; You can take the square root' of gravity; Ideas from the ancient Greeks are resurfacing in a beautiful new form; And the very latest work shows that staying positive' is essential. The book is aimed at a general audience, using analogies, diagrams, and simple examples throughout. It is intended as a brief tour, enabling the reader to become aware of the main ideas and recent work. A full list of further resources is supplied. Bill Spence is the founding Director of the Centre for Research in String Theory at Queen Mary University of London. He has worked on string theory for over three decades.
1. Introduction 2. Everything is Now -- then 3. It's right behind you 4. My donut has no hole 5. Brane waves, or we're just blowing bubbles 6. You are a screen idol 7. Let's twistor again 8. The square root of gravity 9. It's only Platonic 10. Everything is Now -- now 11. Accentuate the positive 12. The future 13. String theory and reality 14. References and further resources
OCLC-licensed vendor bibliographic record.
Keywords: String models; MATHEMATICS / Recreations & Games; SCIENCE / Physics